Monetary and Fiscal Policy Interactions in the Post-war U.S - Yang, Susan (IMF Working Papers; Working Paper ;, 2010)
A New Keynesian model allowing for an active monetary and passive fiscal policy (AMPF) regime and a passive monetary and active fiscal policy (PMAF) regime is fit to various U.S. samples from 1955 to 2007. Data in the pre-Volcker periods strongly prefer an AMPF regime, but the estimation is not very informative about whether the inflation coefficient in the interest rate rule exceeds one in pre-Volcker samples. Also, whether a government spending increase yields positive consumption in a PMAF regime depends on price stickiness. An income tax cut can yield a negative labor response if monetary policy aggressively stabilizes output.